The Effect of Interest Rates and Inflation on Credit Demand through Non-Performing Loans: A Study of Banks Listed on the IDX - Ardhan Ardiansyah Kawakibi; Rita Indah Mustikowati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and test the effect of changes in interest rates and inflation rates on credit demand, with non-performing loans (NPLs) as a mediating variable. The research objects include conventional banks listed on the Indonesia Stock Exchange for the 2019-2024 period. Through purposive sampling technique , 40 banks were obtained that met the criteria as research samples. Data analysis was conducted using the path analysis method to identify direct and indirect relationships between variables. The results of the study revealed that interest rates did not affect NPLs, nor did inflation affect NPLs. Interest rates and inflation also did not affect credit demand. Meanwhile, NPLs had a negative effect on credit demand. However, NPLs were unable to mediate the effect of interest rates and inflation on credit demand. These findings indicate that the NPL level affects credit demand in conventional banks listed on the IDX for the 2019-2024 period.